Role of peer feedback in enhancing students' writing quality / Maizatul Faranaz Md Asif - Md Asif, Maizatul Faranaz (2017)
This study aims to investigate the role of peer feedback in enhancing students‟ writing quality among sixty semester one students of Diploma in Teaching English as a Second Language (TESL) of Kolej University Poly-tech MARA Kuala Lumpur (KUPTM KL). After three hours of peer review training, peer review activity in class and language instructor-student writers conference for each student, the researcher collected students‟ first and revised drafts as well as reviewers‟ written comments. The paired sample t-test revealed that there was a significant difference in the mean scores of first and revised drafts. This suggested that students‟ writing quality improved upon engaging in peer review activity. However, the improvements of students‟ writing quality cannot be attributed directly to the type of changes (meaning changes) they made. The study also revealed that the students produced high percentage of praises in their comments, followed by suggestions and criticisms. In term of their usefulness, students reported in the interviews that praises were the most useful type of feedback given by their peers because they have become more confident and motivated in writing as the result of peer feedback they received. Students in this study also demonstrated positive attitudes towards the use of peer feedback in their ESL writing classroom. However, the study concludes that a successful and effective peer review activity in an ESL writing classroom requires an extensive training for both language instructors and students so that the peer feedback can leave positive impact on students‟ writing quality directly.